Leveraging Technology for Remote Supervision: Overcoming Challenges in Supervising Geographically Dispersed Student Teachers - Gorni, Richard Lionel; Nurdin, Diding; Komariah, Aan (International Journal of Educational Qualitative Quantitative Research, 2024)
Providing effective supervision and evaluation for student teachers during their teaching practice is a significant challenge in developing countries with geographically dispersed placements. This research investigates the impact of distance on supervision and explores alternative supervisory strategies for student teachers at Evangelical Presbyterian University College, Ghana. Utilizing a mixed-methods approach, the study combined an online survey of 100 student teachers with in-depth interviews and observational data. The survey revealed that 55% of respondents experienced difficulties in regular supervisory observations, 60% felt less supported due to physical separation, and 60% reported limited in-person feedback. Interviews highlighted resource constraints and the potential of technology-mediated supervision. Observations of WhatsApp-based supervision sessions demonstrated enhanced communication and real-time feedback, though underscored the need for clear guidelines. The findings suggest that while distance negatively impacts supervision quality, innovative solutions like WhatsApp can mitigate these effects, provided structured protocols are in place. This study emphasizes the importance of integrating technology to enhance teacher education in resource-constrained settings, ultimately improving the teaching practice experience for student teachers. This research contributes information about geographic barriers and the role of technology in helping to create a more inclusive and effective supervision environment for student teachers.